Rancang Bangun Basis Data Spasial Pemantauan Penyebaran Klinik 24 Jam di Dki Jakarta - Indrajani, Indrajani (Bina Nusantara University, 2013)
The purpose of this research is for designing and building spatial database to monitor the spreading of 24 hours clinic in DKI Jakarta. It includes spatial and attributive information for clinics. The benefit of this research is integrating tabular database with spatial database, giving information about the spreading of clinicspatially, and locating new clinics easily in DKI Jakarta. The research method used is data collection such as examine the documents and observation, followed by database analysis and design by Life Cycle (DBLC). The result obtained from this research is a spatial model of database that monitors the spreading of 24-hour clinics in DKI Jakarta. Implementing the new spatial database in monitoring the spread of clinic 24 hours can help the government to increase and develop health service for people in DKI Jakarta.